Enhancing Governance and Community Welfare from the Perspective of Islamic Legal Politics: A Case Study of Musrenbang in Aceh - Muhammad Bin Abubakar; Nanda Herijal Putra (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Langsa, 2025)
This study examines the implementation of the Sub-District Musrenbang (Development Planning Deliberation Forum) in Pandrah, Aceh Province, from the perspective of Islamic political law, with a focus on its role in enhancing community welfare and legitimizing local governance. The research aims to analyze the participation of the sub-district head and community members in planning and executing development programs in accordance with the principles of consultation (syura), justice, and welfare as emphasized in Islamic political-legal theory (maqasid al-syariah). A qualitative method with a descriptive-analytical approach was employed. Data were collected through non-participant observation, unstructured interviews, and documentation, and analyzed to assess procedural implementation, compliance with Islamic legal principles, and the legitimacy of participatory decision-making in local governance. The findings reveal that the musrenbang process contributes significantly to community welfare across sectors such as agriculture, trade, fisheries, education, health, and infrastructure development. The sub-district head coordinates with higher authorities to ensure programs meet public needs, while local residents actively provide input and proposals. Participation grounded in syura strengthens political legitimacy, social justice, and equitable welfare in line with Islamic law. This study contributes to Islamic political-legal studies by illustrating how participatory governance mechanisms operationalize syura and maqasid al-syariah, offering practical guidance for local governments to align development planning with Sharia-compliant social and political objectives.